Influence of the rocking behavior of shearwalls on the fundamental period of CLT structures. (14th January 2021) - Casagrande, Daniele; Pacchioli, Stefano; Polastri, Andrea; Pozza, Luca
Abstract: The comparison of results obtained from on‐site modal tests and numerical analyses presented in recent studies showed that Cross Laminated Timber (CLT) buildings may exhibit a significant shift of fundamental period from the condition when rocking does not occur to the condition which the shearwall rocking is activated for. The objective of the current study is to establish a relationship between the fundamental period of CLT structures and the lateral drift of their global dynamic response. The influence of the activation of rocking behavior on the fundamental period was investigated by using experimental modal testing and Finite Element (FE) numerical analyses. The results from an experimental campaign were adopted to validate an FE numerical model used to perform an extended parametric analysis. The shift of the fundamental period from the value of period representing the condition for which the rocking of shearwall does not occur is investigated via elastic nonlinear incremental dynamic analyses. The effects of vertical load, stiffness, and yield displacement of mechanical anchors and geometrical dimensions of CLT shearwalls are analyzed and discussed. An analytical expression to predict the maximum range of fundamental period which a CLT shearwall may exhibit under different levels of the dynamic lateral response is reported as a function of the vertical load and the equivalent rocking slenderness.